On the sustainability of regional competitiveness development considering risk / Apie regiono konkurencingumo plėtros tvarumą atsižvelgiant į riziką - Aleksandras Vytautas Rutkauskas (Technological and Economic Development of Economy, 2008)
The main goal of the paper is to analyse methodical and practical aspects of country (region) competitiveness sustainable development strategy and its implementation means. Such an innovative problem has raised a lot of original tasks and a need for developing corresponding solution methods. Today definitions of development and sustainability often go together analysing global, regional and local processes. Indeed, in this case the definition of competitiveness, as well as the definition of development sustainability require adequate interpretation and quantitative assessment. In the paper, country (region) competitiveness measure is assumed as three‐dimensional indicator, which depends on the fields of activity, dominating in the country, international economic relations and legal, financial, ecological, natural resources and geographical location environment competitiveness. An assumption is made that it is possible to evaluate quantitatively general competitiveness subject to three mentioned components competitiveness, as well as the competitiveness of every component, subject to the competitiveness of its components, based on generally accepted methods or with the help of expert means. Another assumption is made, that there exist quantitative dependencies among components competitiveness increases and amount of costs required to obtain them. As the instrument of the funds accumulated and developed for integrated country competitiveness indicator increase, evaluation and optimal allocation, the adequate for the decision results reliability assessment portfolio theory is selected, which allows assessing reliability of development possibilities under different levels of risk. Success in risk management is supposed to be factor of the highest importance to tackle sustainability at country's competitiveness development. Final structurisation of expert decision‐making support system principles is discussed when applying the system to competitiveness and risk management.